The effect of catheter‐directed thrombolytic use on readmission rates and in‐hospital outcomes among cancer patients with venous thromboembolism in the United States. Issue 3 (3rd February 2020) - Guha, Avirup; McKinley, Grant; Dey, Amit K.; Carter, Rebecca; Miller, P. Elliott; Deshmukh, Abhishek J.; Zaghlol, Raja; Barac, Ana; Desai, Nihar R.; Addison, Daniel
Abstract: Background: Cancer inducing a hypercoagulable state, venous thromboembolism (VTE) remains a leading cause of morbidity and mortality globally. We assessed the impacts of cancer on the likelihood for readmission after a VTE‐targeted procedure. Methods: We created a new cohort using discharge‐level data from all hospitalizations from State Inpatient Databases of geographically dispersed participating states (18‐27 states). Results: In those presenting with VTE during index‐admission (619 241), 2.4% patients underwent catheter directed thrombolytic therapy (CDL) on index admission and among those 20.3% had cancer. Moreover, the 30‐day readmission rate amongst CDL recipients (10 776 overall) was 14.3% in those with cancer compared to 8.8% in those with no cancer history ( P < .0001). Additionally, in‐hospital mortality (5.7% vs 1.1%; P = 0.009) and cost‐of‐care (11 014 ± 914 vs 10 520 ± 534; P = .04) was significantly higher in cancer compared to noncancer. Conclusion: The use of CDL does not appear to reduce the risk of returning for a VTE‐related admission in cancer.